Culture as the core : perspectives on culture in second language learning - Lange, Dale L.; Paige, R. Michael, 1943- (Research in second language learning., 2003)
This volume presents the very important issue of integrating culture into the second language classroom. Some of its chapters were originally presented at two symposia on culture learning, Interdisciplinary Perspectives on Culture learning in the Second Language Curriculum, held at the University of Minnesota in 1991 and 1994. Other chapters were developed at a third conference, Culture as the Core: Transforming the Language Curriculum. The latter brought scholars and practitioners together to reflect on the earlier theoretical discussions, refine those ideas in light of subsequent theoretical developments, and translate theory into classroom practice.